2014
DOI: 10.1093/hmg/ddu177
|View full text |Cite
|
Sign up to set email alerts
|

Identification of susceptibility loci for colorectal cancer in a genome-wide meta-analysis

Abstract: To identify common variants influencing colorectal cancer (CRC) risk, we performed a meta-analysis of five genome-wide association studies, comprising 5626 cases and 7817 controls of European descent. We conducted replication of top ranked single nucleotide polymorphisms (SNPs) in additional series totalling 14 037 cases and 15 937 controls, identifying a new CRC risk locus at 10q24.2 [rs1035209; odds ratio (OR) = 1.13, P = 4.54 × 10(-11)]. We also performed meta-analysis of our studies, with previously publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(106 citation statements)
references
References 40 publications
(44 reference statements)
3
98
1
Order By: Relevance
“…There was considerable overlap for the number of risk alleles for the simulated people with and without colorectal cancer (for those with colorectal cancer: median 42 [22] 1q25.3 LAMC1 rs10911251 1.05 0.54 1.0006 0.07% [23,24] 1q41 DUSP10; CICP13 rs6687758 1.09 0.2 1.0012 0.15% [25] 2q32.3 NABP1; MYO1B; SDPR rs11903757 1.06 0.36 1.003 0.37% [25,26] 3p14.1 LRIG1 rs812481 1.09 0.58 1.0018 0.22% [27] 3p22.1 RP11; CTNNB1 rs35360328 1.14 0.16 1.0023 0.29% [27] 3q26.2 MYNN; TERC rs10936599 1.08 0.75 1.0011 0.14% [25] 4q26 NDST3 rs3987 1.36 0.44 1.0235 2.87% [28] 4q32.2 FSTL5 rs35509282 1.53 0.09 1.0149 1.83% [29] 5q31.1 PITX1; H2AFY rs647161 1.11 0.67 1.0024 0.30% [30] 6p21.31 CDKN1A rs1321311 1.1 0.23 1.0016 0.20% [18] 8q23. [32,34] 10p13 CUBN rs10904849 1.14 0.68 1.0037 0.46% [22] 10p14 GATA3 rs10795668 1.12 0.67 1.0028 0.35% [31] 10q22.3 ZMIZ1; AS1 rs704017 1.06 0.57 1.0008 0.10% [17] 10q24.2 SLC25A28; ENTPD7; COX15; CUTC; ABCC2 rs11190164 1.09 0.29 1.0015 0.19% [27] 10q25 VTI1A rs12241008 1.13 0.09 1.0012 0.15% [17] 11q12.2 FADS1; FEN1 11qhap ‡ 1.4 0.57 1.0281 3.41% [17] 11q13.4 POLD3 rs3824999 1.08 0.5 1.0015 0.18% [18] 11q23.1 COLCA2 rs3802842 1.11 0.29 1.0022 0.28% [35] 12p13.32 CCND2 rs3217810 1.2 0.16 1.0045 0.55% [23,24] 12p13.32 CCND2 rs3217901 1.1 0.41 1.0022 0.27% [23,24] 12p13.32 CCND2 rs10774214 1.09 0.38 1.0018 0.22% [30] 12q13.13 DIP2B; ATF1 rs11169552 1.09 0.72 1.0015 0.18% [25] 12q13.13 LARP4; DIP2B rs7136702 1.06 0.35 1.0008 0.10% [25] 12q24.12 SH2B3 rs3184504 1.09 0.53 1.0019 0.23% [27] 12q24.21 TBX3 rs59336 1.09 0.48 1.0019 0.23% [26] 12q24.22 NOS1 rs73208120 1.16 0.11 1.0021 0.26% …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was considerable overlap for the number of risk alleles for the simulated people with and without colorectal cancer (for those with colorectal cancer: median 42 [22] 1q25.3 LAMC1 rs10911251 1.05 0.54 1.0006 0.07% [23,24] 1q41 DUSP10; CICP13 rs6687758 1.09 0.2 1.0012 0.15% [25] 2q32.3 NABP1; MYO1B; SDPR rs11903757 1.06 0.36 1.003 0.37% [25,26] 3p14.1 LRIG1 rs812481 1.09 0.58 1.0018 0.22% [27] 3p22.1 RP11; CTNNB1 rs35360328 1.14 0.16 1.0023 0.29% [27] 3q26.2 MYNN; TERC rs10936599 1.08 0.75 1.0011 0.14% [25] 4q26 NDST3 rs3987 1.36 0.44 1.0235 2.87% [28] 4q32.2 FSTL5 rs35509282 1.53 0.09 1.0149 1.83% [29] 5q31.1 PITX1; H2AFY rs647161 1.11 0.67 1.0024 0.30% [30] 6p21.31 CDKN1A rs1321311 1.1 0.23 1.0016 0.20% [18] 8q23. [32,34] 10p13 CUBN rs10904849 1.14 0.68 1.0037 0.46% [22] 10p14 GATA3 rs10795668 1.12 0.67 1.0028 0.35% [31] 10q22.3 ZMIZ1; AS1 rs704017 1.06 0.57 1.0008 0.10% [17] 10q24.2 SLC25A28; ENTPD7; COX15; CUTC; ABCC2 rs11190164 1.09 0.29 1.0015 0.19% [27] 10q25 VTI1A rs12241008 1.13 0.09 1.0012 0.15% [17] 11q12.2 FADS1; FEN1 11qhap ‡ 1.4 0.57 1.0281 3.41% [17] 11q13.4 POLD3 rs3824999 1.08 0.5 1.0015 0.18% [18] 11q23.1 COLCA2 rs3802842 1.11 0.29 1.0022 0.28% [35] 12p13.32 CCND2 rs3217810 1.2 0.16 1.0045 0.55% [23,24] 12p13.32 CCND2 rs3217901 1.1 0.41 1.0022 0.27% [23,24] 12p13.32 CCND2 rs10774214 1.09 0.38 1.0018 0.22% [30] 12q13.13 DIP2B; ATF1 rs11169552 1.09 0.72 1.0015 0.18% [25] 12q13.13 LARP4; DIP2B rs7136702 1.06 0.35 1.0008 0.10% [25] 12q24.12 SH2B3 rs3184504 1.09 0.53 1.0019 0.23% [27] 12q24.21 TBX3 rs59336 1.09 0.48 1.0019 0.23% [26] 12q24.22 NOS1 rs73208120 1.16 0.11 1.0021 0.26% …”
Section: Resultsmentioning
confidence: 99%
“…[32,34] 10p13 CUBN rs10904849 1.14 0.68 1.0037 0.46% [22] 10p14 GATA3 rs10795668 1.12 0.67 1.0028 0.35% [31] 10q22.3 ZMIZ1; AS1 rs704017 1.06 0.57 1.0008 0.10% [17] 10q24.2 SLC25A28; ENTPD7; COX15; CUTC; ABCC2 rs11190164 1.09 0.29 1.0015 0.19% [27] 10q25 VTI1A rs12241008 1.13 0.09 1.0012 0.15% [17] 11q12.2 FADS1; FEN1 11qhap ‡ 1.4 0.57 1.0281 3.41% [17] 11q13.4 POLD3 rs3824999 1.08 0.5 1.0015 0.18% [18] 11q23.1 COLCA2 rs3802842 1.11 0.29 1.0022 0.28% [35] 12p13.32 CCND2 rs3217810 1.2 0.16 1.0045 0.55% [23,24] 12p13.32 CCND2 rs3217901 1.1 0.41 1.0022 0.27% [23,24] 12p13.32 CCND2 rs10774214 1.09 0.38 1.0018 0.22% [30] 12q13.13 DIP2B; ATF1 rs11169552 1.09 0.72 1.0015 0.18% [25] 12q13.13 LARP4; DIP2B rs7136702 1.06 0.35 1.0008 0.10% [25] 12q24.12 SH2B3 rs3184504 1.09 0.53 1.0019 0.23% [27] 12q24.21 TBX3 rs59336 1.09 0.48 1.0019 0.23% [26] 12q24.22 NOS1 rs73208120 1.16 0.11 1.0021 0.26% [27] 14q22.2 BMP4 rs1957636 1.08 0.4 1.0014 0.18% [36] 14q22.2 BMP4 rs4444235 1.11 0.46 1.0027 0.33% [36,37] 15q13.3 SCG5; GREM1 rs11632715 1.12 0.47 1.0032 0.39% [36] 15q13.3 SCG5; GREM1 rs16969681 1.18 0.09 1.0022 0.28% [36] 16q22.1 CDH1 rs9929218 1.1 0.71 1.0019 0.23% [37] 16q24.1 FOXL1 rs16941835 1.15 0.21 1.0032 0.40% [22] 17q21 STAT3 rs744166 1.27 0.55 1.0142 1.74% [38] 18q21.1 SMAD7 rs4939827 1.18 0.52 1.0069 0.84% [35,39] 19q13.11 RHPN2 rs10411210 1.15 0.9 1.0018 0.22% [37] 19q13.2 TMEM91; TGFB1 19qhap ‡ 1.16 0.49 1.0055 0.68% [17] 20p12.3 FERMT1; BMP2 rs2423279, 1.14 0.3 1.0036 0.44% [24,30] 20p12.3 FERMT1; BMP2 rs4813802 1.09 0.36 1.0017 0.21% …”
Section: Resultsmentioning
confidence: 99%
“…Recently, high-throughput single nucleotide polymorphism (SNP) arrays have been used to search for CRC-susceptibility alleles by genome-wide association studies (GWAS) and, to-date, identified 27 genome-wide significant low penetrance loci mapping to 8q24 (13,14), 18q21 (15,16), 15q13 (17,18), 11q23 (16), 10p14 (19), 8q23 (19), 14q22 (20), 16q22 (20), 19q13 (20), 20p12 (20,21), 1q41 (22), 3q26 (22), 12q13 (22), 20q13 (22), 6p21 (23), 11q13 (23), Xp22 (23), 2q32 (24), 12p13 (21,25,26), 5q31 (21), 1q25.3 (24,25), 10q24 (25), 10q22 (26), 10q25 (26), 11q12 (26), 17p13 (26) and 19q13 (26). Studies have suggested that some of these risk alleles may also affect patient survival (27-32); however, none of these survival findings, nor any prognostic biomarkers identified through the candidate gene analyses, have been validated in independent studies (33-35).…”
Section: Introductionmentioning
confidence: 99%
“…With the introducing of advanced molecular techniques e.g. next-generation sequencing multiple genetic defects were investigated through genomewide studies [40][41][42]. In the present study, we were able to investigate 15 genes generally affected in CRC through TruSight sequencing panel (Illumina).…”
Section: Tp53 Showed the Highest Percentage Of Germline Inherited Mutmentioning
confidence: 91%